2015
DOI: 10.1103/physrevlett.114.187801
|View full text |Cite
|
Sign up to set email alerts
|

Collective Ion Dynamics in Liquid Zinc: Evidence for Complex Dynamics in a Non-Free-Electron Liquid Metal

Abstract: A detailed inelastic neutron scattering investigation of the THz dynamics of liquid zinc is presented. The observed Q dependence clearly reveals the existence of a complex dynamics made up of two distinct excitations. The highest energy mode is the prolongation of the longitudinal acoustic density fluctuations whereas the comparison with the phonon dynamics of crystalline hcp zinc suggests a transverse acousticlike nature for the second one. This mode seems related to peculiar anisotropic interactions, possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 31 publications
3
45
0
Order By: Relevance
“…Similar findings were reported from a fit analysis of IXS experiments for liquid Na at temperature 393 K, 14 Cu at 1423 K, 15 Fe at 1823 K, 15 and Zn at 713 K, 15 and another result from INS experiments on liquid Zn at 773 K was reported in Ref. 16.…”
Section: Introductionsupporting
confidence: 89%
“…Similar findings were reported from a fit analysis of IXS experiments for liquid Na at temperature 393 K, 14 Cu at 1423 K, 15 Fe at 1823 K, 15 and Zn at 713 K, 15 and another result from INS experiments on liquid Zn at 773 K was reported in Ref. 16.…”
Section: Introductionsupporting
confidence: 89%
“…Nevertheless, some doubt that HB may be the responsible for shear waves descends from the literature of the last decade, as commented on in a very recent paper 17 . In fact, that work and several papers therein quoted 18 23 have shown that propagating shear modes are not a peculiarity of HB liquids. However, while in some liquid metals 18 23 transverse modes have been detected directly in the dynamic structure factor S ( Q , ω ), this was not the case of liquid gold 24 , where their presence has been assessed 17 only through the analysis of the density of states (DoS) of the liquid, i.e.…”
Section: Introductionmentioning
confidence: 90%
“…It has to be noted that the relationship between collective dynamics and density of states is a general property, not restricted to the longitudinal wave case only. For example, in a recent work [41], the density of states of the crystal phase has been used to interpret dynamic structure factor data of a liquid metal, where an excitation was observed at frequencies close to those of the transverse phonon density of states and was therefore assigned a transverselike character.…”
Section: B Sound Modesmentioning
confidence: 99%